Fiscal Policy During the Demise of Central Planning : The Transition to a Market Economy - Feltenstein, Andrew (Washington, D.C. : International Monetary Fund, 1990)
This paper constructs an intertemporal general equilibrium model designed to examine an economy in transition from central planning to being market oriented. A numerical algorithm is developed to obtain a solution for the model. Simulations using stylized country-specific data examine the effects of price controls during the transition period, as well as of imposing taxes on returns to investment, and on interest earned on private savings. The paper concludes that, under certain circumstances, the taxation of investment as well as of private savings may have positive effects upon consumer welfare, if price distortions are sufficiently severe.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet